The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1586/14737159.2014.916618
|View full text |Cite
|
Sign up to set email alerts
|

Clinical investigational studies for validation of a next-generation sequencingin vitrodiagnostic device for cystic fibrosis testing

Abstract: This is the first systematic evaluation of a NGS platform for broad clinical use as an in vitro diagnostic, including accuracy validation with multiple reference methods and reproducibility validation at multiple clinical sites. These NGS-based Assays had accurate and reproducible results which were comparable to or better than other methods currently in clinical use for clinical genetic testing of cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…[5][6][7][8][9] A number of laboratories have utilized these standards to establish analytical performance metrics for their clinical tests. [10][11][12][13] Validations for targeted disease panels typically include comparison of variant calls to a reference standard, and/or retesting biological specimens containing known pathogenic alterations. [14][15][16] In contrast, validation of WES is typically performed by a methods-based validation approach, which includes comparison of variant calls to reference datasets of genome sequences.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] A number of laboratories have utilized these standards to establish analytical performance metrics for their clinical tests. [10][11][12][13] Validations for targeted disease panels typically include comparison of variant calls to a reference standard, and/or retesting biological specimens containing known pathogenic alterations. [14][15][16] In contrast, validation of WES is typically performed by a methods-based validation approach, which includes comparison of variant calls to reference datasets of genome sequences.…”
Section: Introductionmentioning
confidence: 99%
“…In this tutorial we discussed multiple applications for NGS in clinical oncology including driver identification, detection of resistance mechanisms, quantification of mutational burden, evaluation of tumor gene expression, and diagnosis of germline mutations. The FDA recently approved the Illumina MiSeqDx platform for diagnosis of cystic fibrosis associated mutations, paving the way for approval of NGS‐based tests as CDx assays for oncology indications. In the near term, comprehensive testing of actionable mutations will be accomplished via NGS‐based CDx assays and used to match patients with appropriate targeted therapies.…”
Section: Resultsmentioning
confidence: 99%
“…NGS is already broadly utilized for the detection of germline mutations that cause hereditary illnesses and influence disease risk (e.g., cystic fibrosis) . In the oncology setting, this is particularly useful when sequencing large genes like BRCA1, BRCA2 , and PTEN , or when multiple genes must be tested in the same patient.…”
Section: Applications Of Ngs In Clinical Trials and Clinical Practicementioning
confidence: 99%
“…13 The percentage of diagnoses and the rates of new variant detection are remarkably high in existing studies. [14][15][16][17][18] In the comprehensive study of Grosu et al with two different CFTR kits, the success rate of the tests was found to be between 99.7 and 100.0% compared with Sanger sequencing, which was accepted as the reference method. 14 Apparently, this variant (c.4096A > T, I1366F) was mentioned in two previous studies.…”
Section: Discussionmentioning
confidence: 99%